Developmental venous anomaly coexisting with arteriovenous malformation: a case report - Li, Mei; Ding, JiangBo; Zong, XiTao; Lin, Chi; Liu, QingLing; Chen, XiaoPeng; Wang, JiaXiong (Frontiers in Surgery, 2025)
We describe a rare case of a developmental venous anomaly associated with an arteriovenous malformation. A 20-year-old male presented with seizures and was diagnosed with left parietal arteriovenous malformation combined with developmental venous anomaly in the left frontal lobe, with the draining veins of both lesions converging into the same bridging vein despite the lesions affecting anatomically distinct areas. The patient underwent a craniotomy for resection of the arteriovenous malformation. However, progressive aphasia developed on the third postoperative day. Subsequent neuroimaging (CT and MRI) revealed thrombosis formation within the drainage vein of the developmental venous anomaly. The symptoms of aphasia gradually disappeared after anticoagulant therapy with low molecular weight heparin. This case adds to the current consensus that developmental venous anomalies have normal venous drainage. It also suggests that developmental venous anomalies are susceptible to hemodynamic changes.